Peran Psikologi Kognitif dalam Pembelajaran PAI Anak Usia Dini di PAUD Darussalam - Khairunnisa Ulfadhilah; Aisya, Siti; Nafi’a, Ilman; Hajam, Hajam (Institut Agama Islam Ngawi, 2025)
This study examines the implementation of cognitive psychology principles in Islamic Religious Education (PAI) learning at Darussalam Early Childhood Education (PAUD). Using a qualitative approach with Focus Group Discussion (FGD) techniques involving teachers, parents, and psychologists, this research explores effective learning strategies based on children's cognitive development. The findings indicate that the application of visual and concrete media, direct experiential learning, and structured repetition significantly enhance children's attention, understanding, and memory of religious values. These approaches align with Piaget's cognitive development theory and information processing theory, which emphasize the importance of concrete experiences and repetition in early childhood learning. The study concludes that the integration of cognitive psychology principles into the PAI curriculum creates more meaningful and effective learning experiences. The research suggests the need for developing multimodal learning models and teacher training programs to optimize the implementation of cognitive psychology-based strategies in early childhood Islamic education.